Assessment of the Agro-Input Supply Sector in Kogi State, Nigeria - Sadiq, Mohammed Sanusi; Isah, Musa Ahmad; Abdullahi , Sanni Ozomata; Aliyu, Aishat Ammani (Universitas Ahmad Dahlan, 2022)
Most farmers are experiencing challenges and constraints in accessing agricultural inputs, thus leading to poor and underutilization of agro-inputs and consequently low agricultural productivity in most part of sub-Saharan Africa. This study aimed to assess the agro-input supply sector in Kogi state. A total of 157 input dealers were randomly selected across the twenty-one local government areas in the state. Data were collected using well-structured questionnaire complemented with interview schedule and were analyzed using simple descriptive statistics. Findings reveal that agro-chemicals, fertilizer and feed were the major inputs supplied by most of the retailers and wholesalers that hardly engage in activities that create awareness about their products. Input prices were the most important preference and consideration factor in the purchase of agro-input by customers and form the basis for competition. Casual, family and child labors that proved to be cheaper, commonly accessible and do not require signing of formal employment contract with workers dominated both the retail and wholesale sectors. Poor government support, poor business condition in addition to poor capital base, high transportation cost, price fluctuations, adulteration were the identified major constraints affecting the agripreneurs. The study recommends capacity development on new marketing strategies, registration of businesses with relevant agencies, provision of credit and financial services; formation of formidable, strong and mutual-trust co-operative societies for input supply actors so as to enhance efficiency and effectiveness of the agricultural inputs supply sector in the state.